Influence of Strain Rate and Temperature of Hot Tension Testing on Mechanical Properties of Medium Carbon Steel S48C - Priadi, Dedi; Setyadi, Iwan; Siradj, Eddy S. (Makara Journal of Technology, 2003)
Influence of Strain Rate and Temperature of Hot Tension Testing on Mechanical Properties of Medium Carbon Steel S48C. The characterization of S48C by hot tension testing was done to understanding the influence of temperature and strain rate for S48C flow stress, that close relationship with its forge ability. The hot tension testing was performed on temperatures and strain rates variation (T 850, 900, 950 0C and έ 0,01;1 s-1). The result of hot tension testing showed that increasing temperature decreases ultimate tensile strength (UTS) and flow stress of S48C. The higher decreasing of UTS is on 950 0C about 85% from room temperature condition, while the higher decreasing of flow stress has occurred on 950 0C about 31 % compare to conditions of temperature 850 0C, strain 0,23 & strain rate (έ)1 second- 1 and about 27% compare to the same conditions but έ= 0,01 second-1 . For increasing strain rate from 0,01 to 1 second-1 on the temperature range (850-950 0C) increases UTS about 33 – 50 % and flow stress about 46–53%.